THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE TOWARDS ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION AMONG MINING INDUSTRY EMPLOYEES - Senjaya, Veny; Anindita, Rina (Jurnal Aplikasi Manajemen, 2020)
This study aimed to identify whether transformational leadership and organizational culture could be an appropriate basis for increasing organizational commitment through job satisfaction. This study was conducted through a survey of 320 employees in the mining industry in Jakarta, Indonesia by distributing questionnaires. The structural Equation Model is used to analyze data. The results indicate that there is a positive relationship between transformational leadership and job satisfaction, between organizational culture and job satisfaction, between organizational culture and organizational commitment, between organizational commitment and transformational leadership, and also between job satisfaction and organizational commitment in the mining industry employees. This study is expected to be a reference for further research on the influence of transformational leadership and organizational culture on organizational commitment through job satisfaction and can provide information for consideration in implementing effective human resource management.